B2B e-business models and e-marketplaces : an exploration for SMEs - Çakmaklı, İhsan (My University, 2005)
Firmalar/ İşletmeler arası elektronik ticaret’in yakın gelecekte şirketlerin birbirleri ile ilişki ve ticaret yapma biçimleri üzerinde büyük etkilerde bulunacağı tahmin edilmektedir. Şirketler arası (B2B) ticaret, alıcı ve satıcıların tedarik, üretim’den müşteri ilişkileri ve hizmetlere kadar tüm iş süreçlerinde yeni modellerin uygulanmasını mümkün kılmaktadır. Şirketler, özellikle Küçük ve Orta Büyüklükteki İşletmeler (KOBİ)’in, işletmeler arası ticaret ve elektronik pazaryerlerinin çeşitli nimet ve yararlarından faydalanabileceği ortaya çıkmaktadır. Bu çalışmanın amacı e-iş modelleri ve e-pazaryerlerine uygun teorik modellerin ortaya çıkartılıp KOBİ’ler açısından incelenmesidir. KOBİ’lerin web siteleri, e-pazaryerleri ve e-pazaryerlerinden beklentileri ve görüşlerinin edinimi için anket çalışması düzenlenmektedir. E-ticaret ve B2B incelendikten sonra, B2B iş modelleri analiz edilmiştir. Farklı e-pazaryeri tip ve oluşumları araştırılmıştır. Bu modellere ve e-pazaryerlerine ilişkin, firmalar açısından kritik başarı faktorleri ve belli başlı sorunlar tartışılmıştır. Kobi’lerin genel özellikleri, ekonomideki yeri ve e-ticareti benimsemeye ilişkin durumları incelenmiştir. Kobi’lerin elektronik iş’e geçişleri ve uygulamaları önündeki engeller ve problemler ortaya konmaya çalışılmıştır. Bu konulara ilişkin araştırma ve çalışmalara, bunların sonuçlarına yer verilmiştir. Kobi’ler için öneriler, ilgili kurum ve kuruluşlarınca alınması gereken tedbirlere yer verilmiştir.

Business to Business e-commerce will have an enormous impact on how companies conduct business with each other in the near future. B2B enable buyers and sellers to innovate entire business processes from sourcing, production to customer services. Companies especially Small and Medium Enterprises (SMEs) can profit from various benefits of B2B e-commerce and e-marketplaces. The purpose of the study is to investigate e-business models and theoretical model framework of e-marketplaces especially from the perspectives of SMEs. For this end, an empirical research and survey is carried out to explore the SMEs perceptions and expectations related to websites, e-marketplaces and e-business models. In addition to elaborating e-commerce regarding B2B transactions, B2B business models and specifically e-marketplaces dimensions are explored. Critical success factors in formation of e-marketplaces are also discussed comprehensively to develop the theoretical framework. SMEs and e-commerce adoption of SMEs are examined in depth. Challenges and barriers of e-business implementation of SMEs are also studied to propose the best fit e-marketplace for SMEs. Within this context a research is designed to survey Turkish SMEs to explore the above stated issues concerning B2B e-business models. The sample size of the research is 3719 SMEs, which worths mentioning as the results have considerable generalizability though with some limitations stated in related sections. The results imply that, while some of the success factors of e-marketplaces, B2B models and the level of importance of these factors comply with the previous findings discussed in the literature review, some additional dimensions have been explored to be considered for Turkish SMEs. The importance assessed to dimensions of e-marketplace adoption also show some variations regarding the sectors, size of the enterprise, categorizing themselves as being seller or buyer, their being early adopters of web site presence.
Keywords: e-Ticaret; Küçük İşletmeler; Ticaret